2017
DOI: 10.1007/s13402-017-0330-z
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone suppresses the invasion and migration of breast cancer cells irrespective of their progesterone receptor status - a short report

Abstract: PurposePre-operative progesterone treatment of breast cancer has been shown to confer survival benefits to patients independent of their progesterone receptor (PR) status. The underlying mechanism and the question whether such an effect can also be observed in PR negative breast cancer cells remain to be resolved.MethodsWe performed proteome profiling of PR-positive and PR-negative breast cancer cells in response to progesterone using a phospho-kinase array platform. Western blotting was used to validate the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 27 publications
5
31
0
1
Order By: Relevance
“…We recently showed that progesterone decreases the activation of multiple kinases like EGFR, AKT1 and ERK1/2 in breast cancer cells, leading to suppression of cell migration (19). To test, if NDRG1 mediate inactivation of EGFR/AKT1/ERK1/2 kinases in response to progesterone, we knocked down the expression of NDRG1 in T47D and MDA-MB-231 cells (Figure 10A and 11A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently showed that progesterone decreases the activation of multiple kinases like EGFR, AKT1 and ERK1/2 in breast cancer cells, leading to suppression of cell migration (19). To test, if NDRG1 mediate inactivation of EGFR/AKT1/ERK1/2 kinases in response to progesterone, we knocked down the expression of NDRG1 in T47D and MDA-MB-231 cells (Figure 10A and 11A).…”
Section: Resultsmentioning
confidence: 99%
“…Cells were tested for mycoplasma and were made mycoplasma-free using EZKill Mycoplasma Removal reagent (HiMedia). T47D, BT474, MDA-MB-231, MCF7 and ZR-75-1 cells were cultured as described previously (19,36). The immortalized normal-like 184A1 cell line was cultured in DMEM:F12 medium (HiMedia) supplemented with 28.18IU Insulin, 20ng/ml EGF and 500ng/ml Hydrocortisone.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average pixel density of the duplicate spots for each of the kinases was subtracted from the negative density and was plotted, as detailed earlier. 35…”
Section: Receptor Tyrosine Kinase Proteome Arraymentioning
confidence: 99%
“…The Pixel density of each spot in the array in duplicate was quantified using Image J macro-Protein array analyzer plug in. The average pixel density of the duplicate spots for each of the kinases was subtracted from the negative density and was plotted, as detailed earlier (Godbole et al, 2017).…”
Section: Receptor Tyrosine Kinase Proteome Arraymentioning
confidence: 99%